STRATEGIES TO REVITALIZE GARUDA INDONESIA ROUTE PROFITABILITY TO IMPROVE FINANCIAL PERFORMANCE - Monika, Lidia
PT Garuda Indonesia (Persero) Tbk ("Garuda Indonesia") is an Indonesia flag carrier. In 2011, Garuda Indonesia issued a long term plan: The Strategic Milestones Quantum Leap 2011-2015. The strategy map aims to expand the business massively, including the number of aircraft in service. The target is to increase the number of fleets from 73 aircraft in early 2011 to 194 aircraft by the end of 2015. During this time, Garuda Indonesia also adding three new aircraft types the Boeing 777-300ER (“B777”), Bombardier CRJ1000 Next Gen (“CRJ 1000”), and ATR 72-600. In 2014, the world economy was slow down and directly impacted Garuda Indonesia's massive expansion. Garuda Indonesia report losses USD 399.3 million in 2014.